PENGGUNAAN GERINDA DUDUK MENURUNKAN KADAR KEBISINGAN DAN KELUHAN MUSKULOSKELETAL PADA PANDE BESI DI DESA GUBUG TABANAN - Sri Arjani Ida Ayu Made (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Introduction: Blacksmith is one of the small industries growing in the village of Gubug, Tabanan Regency. These blacksmith craftsmen have been in the job for quite a long time and passed down from generation to generation from their ancestors. They do work as the responsibility of their ancestors. One of the processes in making household tools is small knives, large knives, sickles, and machetes; they are faced with a tool in the form of a grinder. In this process, the worker holding a grinder weighing 1.7 kg vibrates, makes a noise, and sits as is. Working in a noisy environment, being exposed to vibration for a long time is an additional burden that will cause hearing loss complaints and diseases such as Raynaud's Syndrome, Tenosynovitis, and Carpal Tunnel Syndrome. This study aimed to determine the effect of using an ergonomic sitting grinding wheel to reduce noise levels and musculoskeletal complaints in Pande Besi in Gubug Tabanan Village. Methods: This research is an experimental study with treatment by subject design. The population is the small industry workers of Pande Besi in Gubug Village, Tabanan Regency, with as many as 40 people from 10 small industries. The sample is determined based on small industry groups by simple random sampling or simple random sampling with a table of random numbers. The sample size was determined based on the score of musculoskeletal complaints so that the number of small industrial groups was 3.94, rounded up to 4 groups. Each small industry group consists of four people, so the sample size is 16 people. Results: The mean age of the subjects was 49.112±12.15 years, body weight 66.68±6.64 kg, height 162.31±6.78 cm, and body mass index of subjects 25.29±1.71 kg/m2. Statistical analysis showed that there was a significant difference. The average ambient temperature, namely wet temperature, dry temperature, and air humidity, showed no significant difference, noise showed a significant difference, and there was a decrease in the noise of 30.54% before and after using the seat grinder. There was a decrease in complaints of 13.23% after improving the working attitude of the blacksmith. Conclusion: There was a significant decrease between noise levels and musculoskeletal complaints before and after using a seated grinder (p0.05).Keywords: Noise Levels, Musculoskeletal Complaints